2015
DOI: 10.1017/s0021859615000532
|View full text |Cite
|
Sign up to set email alerts
|

Long-term growth of body, body parts and composition of gain of dairy goat wethers

Abstract: SUMMARYThe goal of the present study was to characterize the growth of body parts and composition of the growing empty body to infer how these aspects relate to the long-term growth of goat wethers from dairy breeds. Animals were slaughtered at several ages from birth to maturity (≅900 days old). All body parts were weighed and sampled to determine chemical constituent dry matter, crude protein, crude fat, ash and specific energy. The monomolecular (Brody), Gompertz, and Richards models, a biphasic model forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This decrease occurs in response to a large addition of another constituent in the body; namely fat. Similarly, Araujo et al (2015) reported that the protein content in the EBW of castrated dairy goats decreased as BW increased. Their findings might be related to the large range of BW evaluated (from 5 ± 1.4 to 84 ± 6.5 kg of BW), allowing them to observe fat content up to 396 g/kg of EBW (which was similar to the maximum body fat proportion observed in females herein, 390 g/ kg of EBW).…”
Section: Discussionmentioning
confidence: 87%
“…This decrease occurs in response to a large addition of another constituent in the body; namely fat. Similarly, Araujo et al (2015) reported that the protein content in the EBW of castrated dairy goats decreased as BW increased. Their findings might be related to the large range of BW evaluated (from 5 ± 1.4 to 84 ± 6.5 kg of BW), allowing them to observe fat content up to 396 g/kg of EBW (which was similar to the maximum body fat proportion observed in females herein, 390 g/ kg of EBW).…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that the inflection point of a growth curve represents puberty (the stage of sexual maturation) and afterwards, the growth rate decreases quickly until it reaches zero (Araújo et al ., 2015). In the current study, the inflection point of the BW growth curve occurred at 147 days (4.9 months) for females and 111 days (3.7 months) for castrated males and intact males.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the variance for the model selected for each variable was modelled according to Araújo et al . (2015):where c and φ are the parameters, and μ is the predicted value of the weight of a specific organ. Following these tests, the models with modelled error structure were evaluated using the lowest value of AICc.…”
Section: Methodsmentioning
confidence: 99%
“…The parameter σ refers to the standard deviation, and the term σ 2 refers to the random error variance; thus, Equation 7 represents the homogeneous variance with the assumption of homoscedasticity (25,26). In this case, the homogeneous (Equations 7 and 10), exponential (Equations 8, 11, 13, and 15), and Power-of-the-Means (Equations 9, 12, 14, and 16) variance functions were tested, as they are the most commonly used (27)(28)(29). An attempt to accommodate heteroscedasticity was performed with Equations 8 to 16.…”
Section: Description Of Variance Functions and Combinationsmentioning
confidence: 99%